SARS-CoV-2 testing in North Carolina: Racial, ethnic, and geographic disparities. (May 2021) - Brandt, Katerina; Goel, Varun; Keeler, Corinna; Bell, Griffin J.; Aiello, Allison E.; Corbie-Smith, Giselle; Wilson, Erica; Fleischauer, Aaron; Emch, Michael; Boyce, Ross M.
Abstract: SARS-CoV-2 testing data in North Carolina during the first three months of the state's COVID-19 pandemic were analyzed to determine if there were disparities among intersecting axes of identity including race, Latinx ethnicity, age, urban-rural residence, and residence in a medically underserved area. Demographic and residential data were used to reconstruct patterns of testing metrics (including tests per capita, positive tests per capita, and test positivity rate which is an indicator of sufficient testing) across race-ethnicity groups and urban-rural populations separately. Across the entire sample, 13.1% (38, 750 of 295, 642) of tests were positive. Within racial-ethnic groups, 11.5% of all tests were positive among non-Latinx (NL) Whites, 22.0% for NL Blacks, and 66.5% for people of Latinx ethnicity. The test positivity rate was higher among people living in rural areas across all racial-ethnic groups. These results suggest that in the first three months of the COVID-19 pandemic, access to COVID-19 testing in North Carolina was not evenly distributed across racial-ethnic groups, especially in Latinx, NL Black and other historically marginalized populations, and further disparities existed within these groups by gender, age, urban-rural status, and residence in a medically underserved area. Highlights: Large disparities exist in COVID-19 testing and cases by race and urbanicity in NC. Test positivity was highest in Latino men and increased March to June 2020. Positivity in Black population increased at first, then declined from March to June 2020. Positivity was higher in rural areas than in urban across all groups. Disparities suggest a lag in test availability for historically marginalized groups.